First in human neochordae retensioning for recurrence of mitral regurgitation after neochord procedure - Alessandro Fiocco; Demetrio Pittarello; Augusto D’Onofrio; Florinda Mastro; Gino Gerosa; Andrea Colli (Frontiers in Cardiovascular Medicine, 2023)
The Neochord procedure is a viable option to treat degenerative mitral valve regurgitation in selected patients. Left ventricle reverse remodeling can cause neochord-relative elongation and reprolapse of the treated leaflet, leading to failure. We present a clinical case of extensive ventricle reverse remodeling after neochord implantation and the first-in-man off-pump surgical retensioning of the previously implanted artificial chords.